THE BRAIN IMPRINT: THE NEUROLOGICAL INFLUENCES UPON THE SIGNATURE AND THE HANDWRITING - Ciochină, Claudiu-Dănuț (International Journal of Legal and Social Order, 2026)
The handwriting and the signature constitute essential indentitary elements frequently used in the forensic practice for authenticating documents and identifying persons. Besides their judicial and cultural dimension, these graphic manifestations are direct expressions of the functionality of the central nervous system. The neurobiological features of the act of writing determine a “cerebral print” (Finn E. & al, 2015) that is unique to each individual, reflected in the graphic parameters as pressure, speed, proportions and coherence of the shapes. However, the neurological influences – whether of pathological nature (i.e. Parkinson’s disease, Alzheimer’s, strokes), or of emotional or cognitive nature – can alter the characteristics of handwriting and signature, complicating the forensic examination process. This article aims to analyze the neurobiological mechanisms involved, the way how these are reflected in the handwriting and signature, as well as the practical implications incurred in the graphoscopic expertise and the process of identifying persons.